WTO agreement on agriculture: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
During 2012-13, while the overall process of the World Trade Organization (WTO) trade negotiations remained stalled, a range of agricultural proposals were nonetheless tabled, aimed at providing momentum to break the deadlock. This Executive Brief analyses in details the latest developments prior to the December 2013 WTO Ministerial Meeting in Bali, focusing mainly on the implications for the agricultural sector in ACP countries.